Multiple gene deletions within the human immunoglobulin heavy-chain cluster. - Migone, N (1984)
Two subjects, of 11,000 healthy individuals screened, were found to be missing three and four immunoglobulin isotypes, respectively (IgA1, IgG2, and IgG4; IgA1, IgG2, IgG4, and IgE), and have been analyzed at the DNA level by means of Southern blotting and Ig heavy-chain-specific probes. A broad deletion within the heavy-chain constant region (C) gene cluster was found on chromosome 14 of both probands. Two different haplotypes are described: the first has lost the C alpha 1, C psi gamma, C gamma 2, C gamma 4, and C epsilon genes; the second lacks the C psi epsilon, C alpha 1, C psi gamma, C gamma 2, and C gamma 4 genes. These findings confirm the reciprocal order of the Ig heavy-chain genes as derived by molecular cloning. The inclusion of the C psi gamma gene within the deleted regions confirms its location between C alpha 1 and C gamma 2. From the observed frequency of the homozygous genotype, 1%-3% of healthy subjects from our population are expected to be heterozygous for multiple heavy-chain gene deletions. Cross-over between mispaired homologous regions seems to be the favored mechanism of multiple Ig gene deletions and duplications, and, generally, in the evolution of the human Ig heavy-chain gene family.